Analysis of Implementation Factors and Constraints of Occupational Health and Safety in Multi-Story Building Construction Projects - Kelly, Rully Akbar; Putra, I Nyoman Pahang Dita (Universitas Negeri Padang, 2024)
The implementation of occupational safety and health is one of the key factors in construction project execution, and fundamentally, construction projects involve many hazardous elements. This research aims to analyze the implementation factors and challenges that occur in the application of occupational safety and health (OSH) in high-rise building construction projects by distributing questionnaires to contractors and consultants to obtain data for subsequent analysis. Based on data analysis, nine implementation factors and obstacles in OSH application in building projects were identified, namely workplace safety in the project (X1), equipment and work attire (X2), fire safety (X3), protection of the public (X4), worker health (X5), worker communication (X6), general factors (X7), obstacles from the company's perspective (X8), and obstacles from the worker's perspective (X9). These results were then tested for validity and reliability to determine their validity and reliability, and they were analyzed using descriptive analysis and Pearson correlation analysis. The results of the descriptive analysis indicate that the highest or most frequently implemented OSH factor is the protection of the public (X4) with a mean value of 3.725 and a standard deviation of 0.459. Among the obstacles to OSH implementation, the highest or most frequently occurring factor is the obstacles from the company's perspective (X8) with a mean value of 3.620 and a standard deviation of 0.500. The results of the Pearson correlation analysis show that equipment and work attire (X2) and protection of the public (X4) have the highest correlation value, which is 0.825, indicating a very strong relationship.